2010
DOI: 10.1002/hbm.20996
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced white matter tracts integrity in children with abacus training

Abstract: Experts of abacus, who have the skills of abacus-based mental calculation (AMC), are able to manipulate numbers via an imagined abacus in mind and demonstrate extraordinary ability in mental calculation. Behavioral studies indicated that abacus experts utilize visual strategy in solving numerical problems, and fMRI studies confirmed the enhanced involvement of visuospatial-related neural resources in AMC. This study aims to explore the possible changes in brain white matter induced by long-term training of AMC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
127
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 51 publications
12
127
1
Order By: Relevance
“…In contrast to AD, which signifies axonal morphology, RD implicates the character of the myelin. Decrease in RD implies increased myelination, and increase represents demyelination (2,3,8). This evidence in human neuroimaging studies is consistent with animal studies examining axons and myelination histologically and comparing them directly with DTI results (12, 13).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…In contrast to AD, which signifies axonal morphology, RD implicates the character of the myelin. Decrease in RD implies increased myelination, and increase represents demyelination (2,3,8). This evidence in human neuroimaging studies is consistent with animal studies examining axons and myelination histologically and comparing them directly with DTI results (12, 13).…”
supporting
confidence: 81%
“…In contrast to aging, training in reading, use of the abacus, and working memory have resulted in FA increase by decreasing RD without changing AD. This pattern supports the notion that myelination is the predominant process of the increased FA following training in specific tasks (2)(3)(4). Keller and Just (3) proposed that skill learning would increase neural firing and thus increase myelination (decrease in RD and increase in FA).…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Musicians show positive relations between fractional anisotropy (FA) and training in widespread white-matter regions such as the pyramidal tract (1, 2); however, the opposite result of lower FA in musicians than in nonmusicians in this region of the brain was also reported (3,4). One study has reported that longterm abacus training from an early age enhances the integrity in white-matter tracts related to motor and visuospatial processes (5). Working memory is an important capacity involved in the shortterm maintenance and manipulation of information.…”
mentioning
confidence: 99%